Sensory System for Swarm Drone: A Systematic Review - Amjad Almutairi; Ayat Baroom; Rahaf Alsubey; Salma Elhag (International Journal of Computers and Informatics, 2024)
Drone swarms, or unmanned aerial vehicles (UAVs), are becoming a promising domain in many areas of our lives. They are intricate, multidisciplinary systems, and most research projects concentrate on individual system components for particular use cases. Its involvement in missions and services has shown an imperatively positive influence. This review's objectives are to give a broad overview of the primary applications that spur most research efforts in this area. In our review, we have selected sixty articles between 2019 and 2024 about drone swarms. The review results outline the covered usage fields of drones in the chosen articles. It highlighted communication and control mostly in twenty-seven articles, services in nineteen articles, and tracking in fourteen articles, and we categorized the service domains more specifically as inventory, health care, defense, rescuing, and delivery. Besides that, the simulation aspect has been used for categorization as follows: twelve articles have specified their simulations, thirty-one articles haven’t specified their simulations, and seventeen articles haven’t used simulations. In addition, we have concluded the result of the SWOT analysis for the drone applications.
Keywords: Drone; Unmanned Aerial Vehicles (UAVs); Global Positioning System (GPS); Swarm; Simulation; Services